1995
DOI: 10.1111/j.1476-5381.1995.tb14995.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of the adenosine receptor mediating inhibition of peristalsis in the rat jejunum

Abstract: 1 The non-selective adenosine agonist, 5'-N-ethylcarboxamidoadenosine (NECA), is a potent inhibitor of morphine withdrawal diarrhoea in rats. More recently we found that NECA exerts its antidiarrhoeal effect by inhibiting secretion in both the jejunum and ileum and also by inhibiting peristalsis in the ileum. The specific aim of this study was to characterize the receptor in the rat jejunum mediating inhibition of peristalsis via functional studies using a range of metabolically stable adenosine analogues base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 34 publications
5
16
2
Order By: Relevance
“…The fact that the specific A 1 antagonist DPCPX was able to attenuate the reflex response in the preparations used contrasts with the findings of Hancock and Coupar [31]. Using a different preparation, with reflex stimulation by fluid inflation and recording of longitudinal muscle contraction and of volume expulsion, they were unable to find any influence of the A 1 antagonist DPCPX on the peristaltic reflex response [31]. This difference might be due to different experimental set-ups (electrical vs. fluid inflation), to the use of different muscle layers to record contractile activity (longitudinal vs. circular smooth muscle), or possibly to the fact that different regions were investigated (ileum vs. jejunum).…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…The fact that the specific A 1 antagonist DPCPX was able to attenuate the reflex response in the preparations used contrasts with the findings of Hancock and Coupar [31]. Using a different preparation, with reflex stimulation by fluid inflation and recording of longitudinal muscle contraction and of volume expulsion, they were unable to find any influence of the A 1 antagonist DPCPX on the peristaltic reflex response [31]. This difference might be due to different experimental set-ups (electrical vs. fluid inflation), to the use of different muscle layers to record contractile activity (longitudinal vs. circular smooth muscle), or possibly to the fact that different regions were investigated (ileum vs. jejunum).…”
Section: Discussioncontrasting
confidence: 85%
“…The ascending contractile response is increased by the A 1 agonist CPA at lower concentrations, whereas it is attenuated at higher concentrations. This finding is different compared to studies focused on the peristaltic reflex and peristalsis, in which activation of A 1 receptors causes an attenuation of the ascending contraction in guinea-pig ileum [30] or a decrease in peristalsis in rat jejunum [31] but direct comparison in this case is hampered by the different setups, different species and the different and higher agonist concentration used. The experimental set-up used in the present study also showed an attenuation of the ascending contractions, but only at high concentrations – an effect that may be nonspecific, whereas at lower concentrations the effect of CPA has to be regarded as a specific A 1 receptor-mediated effect.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…These findings support previous in vivo data showing that DPCPX, a selective A 1 receptor antagonist, markedly enhanced gut propulsion. A 2a receptors mediate facilitatory effects on acetylcholine release in rat ileum, while A 2b receptor stimulation results in a marked inhibition of peristaltic activity in rat small bowel 84–86. Although there is evidence of A 3 receptor expression in rat jejunum,87 data on their possible role in the regulation of gut motility are lacking.…”
Section: Dysregulation Of Gut Motor Functions Associated With Bowel Imentioning
confidence: 99%
“…In addition, the efflux of adenosine from cells is normally increased in the face of damage, and it might be anticipated that increased local levels of adenosine might arise in inflammatory disease states. The increased adenosine could then modify neuronal activity by acting directly on the cell membrane to depolarise or hyperpolarise [1,2,5,6,41] or to modify the release of enteric neurotransmitters, with A1 receptors depressing and A2A receptors enhancing the release of classical and non-cholinergic, non-adrenergic transmitters [2,16]. There is also accumulating evidence for the effects of adenosine on both ion secretion [8] and cell proliferation and survival [18] in the intestinal epithelium, leading some authors to propose that adenosine may be an endogenous regulator of these functions and may be involved in the aetiology of bowel disorders.…”
Section: Purinesmentioning
confidence: 99%